نظرية المعرفة؛مكانتها وأهميتها في الفكرين الفلسفي والصوفي - Andi Muhammad Ridwan Thahir; Islamul Haq (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2017)
The purpose of this research is to uncover the theory of ma`rifah in terms of its place and importance in philosophical and mystical thought. The theory of ma`rifah occupied a place of importance in human thought. There is no school of thoughts, whether philosophical or religious, except for it. In the field of philosophy, the theory of ma`rifah is one of the most important theories and the most prominent philosophical detective, but the mystics have also been the theory of ma`rifah also occupies a position of great importance, as they reveal the truth of the ways the Sufi to know God, and knowledge of God in these are the measure of human wellbeing and the secret of superiority over others Other creatures, the degree of ma`rifah reached by any one of the scale of the news of his salary in life.